Peran Status Sosial Ekonomi terhadap Performa Akademik dari Perspektif Peserta Didik di SMK Negeri 1 Tondano - Tani, Brigita Junainsi; Subuh, Hairun; Pangalila, Theodorus (CV. Kurnia Grup, 2024)
This study aims to analyze the role of students' socioeconomic status on academic performance from the perspective of students at SMK Negeri 1 Tondano, especially in the subjects of Civic Education and Information and Communication Technology. So that it can provide insight for the development of more inclusive and equitable education policies at SMK Negeri 1 Tondano. The method used is qualitative with a case study approach, involving interviews, observation and documentation. Results show that students from high SES families have better access to educational resources and greater support, while students from low economic backgrounds face challenges that hinder their achievement. The research conclusion confirms the importance of considering socioeconomic well-being in designing education policies so that all students have equal opportunities to succeed.